2003
DOI: 10.1159/000075256
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Spinal Involvement in Neuroblastoma Patients

Abstract: Introduction: Considerable controversy exists regarding the appropriate management of spinal involvement in neuroblastoma (NB) patients. We review a large group of such patients and offer treatment recommendations. Methods: Forty-six patients with epidural and/or neural foraminal involvement treated between 1987 and 1998 were staged according to the International NB Staging System (INSS) and classified as high-risk (INSS stage 4; n = 31) or low-risk (INSS stage <4; n = 15). Of 13 high- risk patients with norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 10 publications
0
17
2
2
Order By: Relevance
“…Parikh et al 79 reported on 22 patients, 19 of whom attained a favorable outcome and long-term survival. Sandberg et al 87 concluded that high-risk neuroblastoma patients with high-grade spinal cord compression may respond to chemotherapy, but a percentage will require surgical decompression for progressive neurological deficits. For patients at low risk, the 5-year survival rate is greater than 95%; for those in the intermediate-risk group, the rate is between 90% and 95%; and for those in the high-risk group, the rate is between 40% and 50%.…”
Section: Neuroblastomamentioning
confidence: 99%
“…Parikh et al 79 reported on 22 patients, 19 of whom attained a favorable outcome and long-term survival. Sandberg et al 87 concluded that high-risk neuroblastoma patients with high-grade spinal cord compression may respond to chemotherapy, but a percentage will require surgical decompression for progressive neurological deficits. For patients at low risk, the 5-year survival rate is greater than 95%; for those in the intermediate-risk group, the rate is between 90% and 95%; and for those in the high-risk group, the rate is between 40% and 50%.…”
Section: Neuroblastomamentioning
confidence: 99%
“…In the last decade, researchers have used a variety of techniques to study brain reorganization in children with cerebral palsy, including functional magnetic resonance imaging, magnetoencephalography (MEG), transcranial magnetic simulation, diffusion tensor imaging, and near infrared spectroscopy. 1 These studies (like the MEG study by Nevalainen et al 5 ) help us understand cortical reorganization in cerebral palsy and provides a glimpse of the clinical consequences of neuroplasticity processes.…”
mentioning
confidence: 99%
“…There is considerable debate about advantages and disadvantages of these treatment options and treatment algorithms vary among institutions. [2][3][4][5] In the largest cohort of children with neuroblastoma and spinal cord compression published so far (n=122), Simon et al 6 try to clarify the controversial issues about the emergency treatment of choice in these children. To achieve this aim, the authors retrospectively analyzed the short-and longterm outcomes of patients with neuroblastoma and spinal cord compression included in four consecutive prospective German clinical trials.…”
mentioning
confidence: 99%
See 2 more Smart Citations